Flexural performance of squared one-sided CFRP patches: modelling and experimental study - Abdelfattah, Ibrahim (2022)
Three-point bending analysis, experimental and numerical, is conducted for three different sizes, 30*30 mm, 40*40 mm and 60*60 mm, of one-sided square cross-ply TEXIPREG HS 160 RM carbon-fiber-reinforced polymer (CFRP) patches as well as intact and notched specimens. The tests are carried out with the aim to study the influence of the patch’s size on the flexural properties of the specimen. Hashin-2D damage initiation criterion is adopted to investigate the failure in each ply, and the damage evolution is represented by the stiffness degradation. The intact and notched laminates flexural properties are investigated as well as notch sensitivity. The bonded patch repairs efficiency is investigated in the light of ultimate load, flexural modulus, peel and shear stresses along the bond-line as well as the damage initiation coefficient at critical zones. A significant advancement in the flexural modulus and ultimate load for the repaired laminates is noticed with increasing the patch’s size. A Parametric numerical study is conducted to investigate the influence of the patch size on the damage initiation coefficient at the critical zones. The recommended patch’s size is 44*44 mm in order to avoid failure initiation at the patch corner overlap on the parent laminate.